2017
DOI: 10.7205/milmed-d-16-00134
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Responsiveness, and Criterion Validity of the Kiio Sensor, a New Tool for Assessment of Muscle Function

Abstract: Musculoskeletal injuries are a leading cause of disability in both the general population and military, and the ability to effectively quantify musculoskeletal function remains problematic. The aim of the current study is to investigate the reliability, responsiveness, and criterion validity of the kiio Sensor for measurement of muscle strength, a key aspect of comprehensive functional assessment. Forty-four (24 male, 20 female) physically active civilian adults (mean [SD] = 21.2 [1.5] years of age) with no hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…All 21 studies evaluated reliability in a test-retest design. 6,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] We present the summarized results, the overall rating of the results, and the quality of evidence in the summary of findings table (table 3). Most studies reported the ICC, but 5 studies used Pearson correlation coefficient, variability, or coefficient of variation.…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…All 21 studies evaluated reliability in a test-retest design. 6,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] We present the summarized results, the overall rating of the results, and the quality of evidence in the summary of findings table (table 3). Most studies reported the ICC, but 5 studies used Pearson correlation coefficient, variability, or coefficient of variation.…”
Section: Reliabilitymentioning
confidence: 99%
“…Measurement error was investigated in 13 studies. 6,[21][22][23][24][25]27,29,31,34,[36][37][38] The summarized results, the overall rating of the results, and the quality of evidence are presented in the Summary of Findings table (table 4). Seven studies reported SEM only as an absolute value but provided sufficient data to calculate the %SEM.…”
Section: Measurement Errormentioning
confidence: 99%
“…Fortunately, there are tools that provide more objective and accurate results. Commonly referred to as the “golden standard”, are the isokinetic dynamometers (ID) such as the Cybex II isokinetic dynamometer [ 11 , 12 ]. However, their clinical use is limited, due to their high cost, non-portability, and their complicated setup and operation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly referred to as the “golden standard”, are the isokinetic dynamometers (ID) such as the Cybex II isokinetic dynamometer [ 11 , 12 ]. However, their clinical use is limited, due to their high cost, non-portability, and their complicated setup and operation [ 12 ]. Similarly, the load cell, coupled with a signal conditioner, is a laboratory setup commonly used to accurately measure isometric muscle strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation